PENERAPAN QUANTUM LEARNING UNTUK MENINGKATKAN MOTIVASI DAN PENGUASAAN KONSEP IPA SD - Dini Haryanti; Sheryl Mutiara Putri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This literature research aims to examine the potential of the Quantum Learning learning model in increasing learning motivation and mastery of Natural Sciences (IPA) concepts in elementary school students. The research background identifies the problem of low motivation and understanding of science concepts due to conventional learning that tends to be passive and focuses on memorization. The Quantum Learning model, with its fun, empowering, and holistic approach, is considered relevant to address this problem. The method used is literature review, analyzing various trusted sources to understand the theoretical foundations and empirical findings related to Quantum Learning, learning motivation, and mastery of science concepts at the elementary level. The results of the literature review show that the Quantum Learning model has the potential to increase student learning motivation through the creation of a positive, interactive, and relevant learning atmosphere to daily life. This increase in motivation is expected to be positively correlated with a deeper mastery of science concepts because students are more actively involved, have high curiosity, and build understanding through various learning styles. Nonetheless, the implementation of Quantum Learning requires skilled teachers, adequate facilities, and careful planning. This study concludes that the Quantum Learning model is worth considering as an innovative strategy to increase the motivation to learn and mastery of science concepts for elementary school students, by paying attention to the readiness of its implementation.